2014
DOI: 10.2478/s11536-013-0336-5
|View full text |Cite
|
Sign up to set email alerts
|

Spinal hyperbaric prilocaine vs. mepivacaine in perianal outpatient surgery

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Previous study done by Gebhardt et al suggested that hyperbaric prilocaine had faster recovery from spinal anaesthesia when compared with mepivacaine. (Gebhardt et al, 2014) Figure 11: Bar graph depicting the association between the awareness of effective use of hyperbaric prilocaine and age groups. X axis -age in years; Y axis-number of students with their responses.…”
Section: Methodsmentioning
confidence: 99%
“…Previous study done by Gebhardt et al suggested that hyperbaric prilocaine had faster recovery from spinal anaesthesia when compared with mepivacaine. (Gebhardt et al, 2014) Figure 11: Bar graph depicting the association between the awareness of effective use of hyperbaric prilocaine and age groups. X axis -age in years; Y axis-number of students with their responses.…”
Section: Methodsmentioning
confidence: 99%
“…Since 2009, a new and stable formulation of 2% hyperbaric prilocaine for intrathecal administration has been developed and increasingly used in day-case surgery setting. The ever-growing use of this drug led to several studies deining the optimal doses for diferent types of surgery (Gebhardt et al 2013(Gebhardt et al , 2014Kaban et al 2014;Guntz et al 2014). Metabolism of prilocaine and particularly its downstream metabolite o-toluidine was also studied (Fig.…”
Section: Introductionmentioning
confidence: 99%